Modular Framework for Crowd Simulation “Menge” from a Production Warehouse Simulation Perspective - López, Irving; Rivera Zarate, Gilberto; Rafael, Saldaña (Springer, 2021)
The topic of warehouse optimization is a critical and popular topic within the scientific literature. Particularly, order-picking optimization presents several profound difficulties: modeling, analysis, and data representation. Althoug these are necessary and obvious requirements for any research project, the visualization is an important aspect that has its challenges and complications. Menge is an open-source platform for crowd simulation. It provides an extensible common for research and development. In the present study, it is shown how the simulation platform known as Menge was adapted as a possible complement to the optimization process for the simulated visualization of its results. This chapter presents a solution using Menge to separate the modeling for the routing algorithm from visualization and simulation programming. The purpose of this work is to establish a starting point of industrial simulation in collaboration with algorithms for order-picking optimization in warehouses.